Experimental Method For Determining The Parameters Of A Device For Applying A Polymer Composition On The Stitches Of Materials - Behbudov Shavkat Husenovich; Sapayev Rustam Atanazarovich; Xadjayev Qudrat Sherzadovich (Research Parks Publishing LLC, 2021)
The article provides a device for applying a polymer composition to the lines of the materials being ground. The dynamics of the machine unit is considered, the laws of motion of the rollers of the device are determined, the recommended parameters of the system are substantiated on the basis of the analysis of graphical dependencies.